PROBLEMS IN THE TREATMENT OF PATIENTS WITH SUPUPORATIVE LIVER DISEASES AND THEIR TREATMENT TACTICS - Kasimov U.K; Boboev K.X. (Scholar Express Journals, 2024)
The presented work analyzes the results of treatment of 168 patients with liver abscesses, who were hospitalized in the TMA multidisciplinary clinic, for the period from 2015 to 2022. The main instrumental methods of investigation were: Ultrasound and multispiral computed tomography. To date, minimally invasive interventions are highly effective, subject to adequate local sanation and targeted antibiotic therapy. These operations must be performed in specialized institutions and by high-level specialists, since repeated punctures with an attempt of catheterization result in traumatization and complications development; the recommended tactics of patient management allows to stop the inflammatory process, with adequate clearing of abscess cavity. Inclusion of prolonged intra-arterial catheter therapy in the complex of therapeutic measures at the stage of infiltration allows to prevent abscess formation
Keywords: Liver abscess; errors; prolonged intra-arterial catheter therapy